Continuous Subcutaneous Insulin Infusion (CSII): Impact on Metabolic Control and Quality of Life of the Informal Caregiver - Rangel,Maria Adriana (2018)
Aim: To describe the population of children treated with Continuous Insulin Subcutaneous Infusion (CSII) in a single-center unit and assess the impact on metabolic control. As an additional purpose, we also assessed the perceived burden of the caregivers of children with type 1 diabetes (T1DM) and correlated with the insulin delivery method (CSII vs. multiple daily injections - MDIs). Methods: Descriptive, cross-sectional, observational study, of all patients with T1DM under CSII treatment, followed in a Pediatric Endocrinology Clinic between January 2011 and September 2016. Outcomes regarding metabolic control were assessed at three points: on initiation of CSII, after three to six months period and at the last appointment. On a second phase of our study, we applied the Informal Caregiver Burden Assessment Questionnaire, drawn and validated for the Portuguese population, to parents of children under CSII and compared them with a sample of parents of children under MDIs. Results: Of a total of 112 T1DM patients followed, 22 patients under CSII treatment were included, with a mean HbA1c of 7.6 ± 0.9%. CSII use was associated with a reduction on body mass index (BMI) z-score over time, and no differences on HbA1C, blood pressure (BP) and lipid profile. Frequency of severe hypoglycaemia and number of hospitalization for metabolic decompensation were significantly reduced. A total of 44 caregivers answered the questionnaire, aged between 27-52 years, the majority of the female gender (77.3%). The overall overload perceived was not high (Median [Md]=23.0%; Interquartil range [IQR]: 9.8-35.7). Emotional overload (Md=34.4%), family support (Md=25.0%) and personal life implications (Md=23.9%) were the dimensions that contributed the most to the negative overload felted. When compared between groups (n=20 CSII; n=24 MDIs), there were no differences in total or partial quotation. Conclusion: CSII was associated with a reduction in BMI z-score, number of severe hypoglycaemia and hospitalization, with no differences in HbA1C, BP or lipid profile. Although many studies indicate an improvement in the quality of life of children with CSII and their caregivers, our study does not point to a reduction in the overload experienced. Addressing caregiver psychological distress and burden, ideally through specific and validated diabetes questionnaires, in family-based treatments such as T1DM are of valuable interest and may improve, overtime, health outcomes.